2007
DOI: 10.5962/bhl.title.113914
|View full text |Cite
|
Sign up to set email alerts
|

Campbell Creek timber - grazing demonstration : cattle use of regenerating deciduous cutblocks /

Abstract: This project involved the use of ten Global Positioning System (GPS) collars to monitor cattle grazing behaviour and habitat use across a diverse mosaic of forested and non-forested range plant community types including regenerating aspen forest. Cattle use of all native plant community types was secondary to tame forages, including aspen cutblocks. If there are other community types available that are preferred above regenerating deciduous communities cattle are unlikely to use cutblock areas until forage is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…Livestock were attracted to tame pasture areas. In the absence of proper management, they may have tended to graze these areas to the exclusion of all other native plant areas until the tame forage resource was consumed (Pitt et al 1998, Hincz 2007. The data showed that the greatest change in the time spent was between the tame pasture zone and the 25 m buffer zone.…”
Section: Conclusion 361 Bear Mountainmentioning
confidence: 73%
See 4 more Smart Citations
“…Livestock were attracted to tame pasture areas. In the absence of proper management, they may have tended to graze these areas to the exclusion of all other native plant areas until the tame forage resource was consumed (Pitt et al 1998, Hincz 2007. The data showed that the greatest change in the time spent was between the tame pasture zone and the 25 m buffer zone.…”
Section: Conclusion 361 Bear Mountainmentioning
confidence: 73%
“…GB was very diverse in its community types, the forage species and availability of the forage species also varied. When the cattle moved through an area, they grazed their preferred species first and then move on to their secondary choices (Hincz 2007). This would cause cattle in GB to have to move through areas of less preference to get to primary forage species, thus resulting in cattle spending more time in areas further from the tame pastures.…”
Section: Conclusion 461 Elliot's Creekmentioning
confidence: 99%
See 3 more Smart Citations